The Student’s Errors in Mathematical Problem Solving Based on NEA Judging from the Self Efficacy on Learning CORE - Cahyani, Hesti; Suyitno, Hardi; Junaidi, Iwan (Unnes Journal of Mathematics Education Research, 2020)
The purpose of this study were (1) to describe the quality of learning with models CORE of the errors made by students in solving mathematical problems and (2) to describe the students' errors in solving math problems by NEA in terms of self-efficacy categories of high, medium, low on the model of CORE. This study uses concurrent design embeddes. The population in this study was all students of class VIII SMP Negeri 1 Kalikajar, Wonosobo. Data collected through the data collection of quantitative and qualitative data collection. The results showed that (1) the quality of learning through CORE model of good category, and (2) the student category higher self-efficacy has a pattern of phase transformation and encoding errors. Student’s category of self-efficacy was a pattern transformation phase error, process skills and encoding. Student self-efficacy lower category still make errors at this stage of reading, transformation, process skills, and encoding, but there is increased when writing down all the stages in detail.